Anterolateral tibial plateau osteotomy as a new approach for the treatment of posterolateral tibial plateau fracture: A case report. Issue 3 (January 2018) - Sun, Da-Hui; Zhao, Yi; Zhang, Ji-Ting; Zhu, Dong; Qi, Bao-Chang
Abstract: Rationale: It is challenging to visualize and reduce a posterolateral tibial plateau fracture through an anterolateral approach as the tibial plateau fragments are often covered by the fibular head and ligamentous structures. Patient concerns: In this case report, we describe a patient with a depression fracture of the posterolateral quadrant combined with a split fracture of the posteromedial quadrant and an avulsion fracture of the tibial intercondylar eminence. Diagnoses: Tibial plateau fracture(AO type 41-B3). Interventions: A posteromedial approach combined with an anterolateral approach and an osteotomy involving the proximal tibiofibular joint of the tibial plateau was used to expose, reduce, and fix the fracture. Outcomes: There was no risk of injury to the common peroneal nerve or ligaments. The patient is recovering well and is satisfied with the function of the injured knee. Lessons: We recommend anterolateral tibial plateau osteotomy for the treatment of posterolateral tibial plateau fractures in clinical practice.